Theoretical and experimental investigation on single and double bolted bamboo joint under axial tension - Sonar, I. P.; Siddhaye, V. R. (Journal of Structural Engineering, 2025)
Bamboo is the strongest known natural fiber material available abundantly in the world. Highest growing and yielding rate, resistance to weathering action, high strength to weight ratio make the bamboo a versatile material for temporary or semi permanent low cost construction. Considering physical and strength properties of bamboo, it can be used as the structural member for plane and space trusses such as truss, grid, dome, etc used as roof-supporting structures. Different types of bamboo joints for round bamboo have been suggested by researchers. Use of half splint bamboos as structural members and joints with mild steel plate as gusset is an innovative concept suggested by the first author. An extensive experimental program was undertaken by the author to determine various mechanical properties of (Dendracalamus Strictus) bamboo and to examine the behavior of single bolted connection of bamboo under axial tension. Based on the test results, further theoretical investigation on the development of double bolted bamboo joint is carried out. To verify the strength and efficiency of these bamboo joints under axial tension, specimens with double bolted joint were tested under axial tension and results are compared with theoretical values. It is observed that experimental load carrying capacity of the proposed member and joint is more than predicted value. Considering strength capacities of the suggested bamboo steel composite joint and member, it has enough potential by giving proper treatment to replace conventional steel angle sections for plane and space trusses for construction of temporary and semi-permanent structures.